Size factors as determinants of recurrent unit cost of public secondary education in Edo State, South-South Nigeria (2016)
This study, investigated the influence of school size factors (enrolment, average-class-size and student-teacher-ratio) on the recurrent unit cost of public secondary education in Edo State, Nigeria. The study adopted the descriptive survey design. This design was considered appropriate because it provided a strategy for obtaining and describing the existing conditions without any manipulation. The multi-stage sampling techniques were used to select 207 out of the total 509 conventional public secondary schools across the State. Two inventories were used to collect secondary data from the 207 schools and the State Ministry of Education officials. The school inventory was used to obtain data on individual school size features and recurrent expenditures while the inventory for Ministry of Education was used to collect aggregate school enrolment, classes, staff and recurrent expenditures. Two research questions were raised, while data were analyzed using the multiple regression technique. Result indicate that Size factors had significant influence on the recurrent unit cost of public secondary education (F(5.163)=32.6: p<0.05). They jointly accounted for 49% of the Variation in recurrent unit cost. The relative contributions of the independent variables were as ranked: enrolment (ß = -0.71; t= -6.14; p<0.05), student-teacher-ratio (ß= -0.66; t= -3.34; p<0.05) and average-class-size (ß = -0.40; t= -1.75; p<0.05). This implied that enrolment and student-teacher-ratio factors were the strongest predictors of unit cost. All the three size factors were inversely related to unit cost. A marginal unit increase in enrolment; average-class-size and student-teacher-ratio reduced recurrent unit cost by N113.92, N234.01 and N584.85 respectively. The relationship between expanding the size factors and recurrent unit cost was U-shaped, indicating that there were Optimum sizes for the various size factors. These were: enrolment- 712 students per school, average-class-size- 45 students and student-teacher ratio- 50:1 respectively Enrolment and Student-teacher-ratio factors had significant influence in the reduction of recurrent unit cost of public education. Therefore, enrolment and student-teacher-ratio could be increased to the Optimum level as a cost reduction strategy in public schools. This could be achieved through merger of small-sized inefficient schools